Reaction and free-energy pathways of hydrogen activation on partially promoted metal edge of CoMoS and NiMoS: A DFT and thermodynamics study - Chanchai Sattayanon (2018)
© 2017 Elsevier B.V. Understanding of molecular hydrogen (H2) activation mechanism on MoS2-based catalysts is crucial for enhancement of catalytic hydrotreating processes. In this work, H2activation reaction pathways including adsorption, dissociation, and diffusion phases on metal edge of partially Co-promoted MoS2(CoMoS) and partially Ni-promoted MoS2(NiMoS) catalysts under hydrotreating conditions have been investigated using density functional theory and thermodynamic calculations. Here, investigation of H2adsorption on CoMoS and NiMoS catalysts shows that H2molecule prefers to adsorb on the promoter site rather than the sulfur site, while the H2molecule adsorbs firmly on CoMoS but substantially weaker on NiMoS. H2dissociation is the rate-determining step for both CoMoS and NiMoS catalysts and the activation energy (Ea) of rate-determining step for both catalysts is identical (Ea = 0.79 eV). However, thermodynamic result indicates that CoMoS is more reactive toward H2activation than NiMoS (free energy of activation (ΔG‡) at 575 K = 0.65 and 1.14 eV for CoMoS and NiMoS, respectively). In terms of diffusion, hydrogen atom migrates relatively easy (Ea < 0.55 eV) on both CoMoS and NiMoS surfaces. Partial charge analysis reveals that both heterolytic and homolytic H2dissociation characteristics are observed on CoMoS and NiMoS depending on the reaction site. In addition, dissociated hydrogen atoms are more stable in terms of thiol group (S[sbnd]H) on CoMoS while metal-hydrogen pairs (Mo[sbnd]H and Ni[sbnd]H) are more stable on NiMoS.